Investigating the cooling effect of the inlet flow on the axial compressor performance in different operating conditions - Sarallah Abbasi; Moein Salmani (Scientific Reports)
Abstract In this article, the compressor performance in wet compression conditions is compared with that of dry compression. Wet condensation has been done through droplets with one-micron diameter and a three percent mass flow rate. The flow inside the compressor is steady and three-dimensional, using the software ANSYS CFX has been simulated. In the case of wet compression, the discrete phase transition model has been used along with the application of active input forces from the continuous phase. The comparison of the present simulation results for dry states with the experimental data reports a good agreement. The results indicate that applying wet compression in the compressor improves adiabatic efficiency by 7.21% in near-stall conditions, 5.21% in design conditions, and 1.78% in choking conditions. The use of wet compression significantly reduces the mass flow rate under operational conditions of choking, it is not recommended to use this method in the operational conditions of choking in the compressor. The results indicate that the compressor stable performance range is reduced by 18.31% with wet compression compared to dry compression, which is unfavorable. Also, the stall margin of the process of wet compression and dry compression was obtained as 2.38% and 8%, respectively. The results of the study showed that with flow injection, the stall margin of the wet compression process was reduced by 5.62% compared to the dry compression process.